BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA GURU DI MTS NEGERI BATU DAN SMP AR-ROHMAH PUTRI MALANG, JAWA TIMUR - Sri Harmonika (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2016)
Organizational culture is one of the aspects that determine the success of an organization. Cultures distinguish people from one another in how to interact and act complete a job. Cultural binding members of the community into one unified view of creating uniformity behave or act. Culture will affect the performance and behavior of the organization, one of which affects the increase in teacher performance. Improved performance of teachers is a must for educational institutions who wish to survive all time, because teachers in educational institutions is the key to the success of the learning process. This study aimed to analyze and examine (1) the type of teacher performance and other forms of organizational culture that develops in improving the performance of teachers at MTs Negeri Batu and Junior High School Ar-Rohmah Malang, (2) the development of organizational culture in improving the performance of teachers in MTs Stone and SMP Negeri High School Ar-Rohmah Malang, (3) the impact of organizational culture in improving the performance of teachers at MTs Negeri Batu and Junior High School Ar-Rohmah Malang. This study used a qualitative approach with case study design multikasus. Data collection method is observation, interview and documentation. Data were analyzed using data analysis Miles and Huberman model that includes four components: data collection, data reduction, data presentation and conclusion. Checking the validity of the data using Credibility, Transferbility, Dependebilitas, and confirmability. The results of this research: 1) The shape of the cultural values of the organization that developed at MTs Negeri Batu and Junior High School Ar-Rohmah daughter Malang, among others, the motivation need of power and the need for achievement, discipline, unity, obedience, pray, adab studying, mutual respect 2) The process of cultural development organization in improving performance both school teachers conducted by five phases namely a) the desire of change is based on the value transendent / religious leader and a strong desire; b) preparing (preparation) through the [1]development of systems and cultural mindset; c) unfreezing (liquefaction) is done through continuous socialization, coaching cadre and non-cadre, as well as reward and punishment; d) movement (move) through motivation and encouragement; e) Refreezing (freezing) through a process of habituation and commitments 3) The impact of organizational culture in improving teacher performance both schools a) For the teacher began to grow the value of labor discipline, growing mutual respect and appreciate, b) For students begin to grow more diverse both academic achievement and non-academic c) For the community began to grow interest and public trust.